Troubled by the Humics : Effects of water colour and interspecific competition on the feeding efficiency of planktivorous perch - Estlander, Satu; Horppila, Jukka; Olin, Mikko; Vinni, Mika; Lehtonen, Hannu; Rask, Martti; Nurminen, Leena (Finnish Environment Institute, 2017)
Peer reviewed